The importance of academic monitoring in the rise to teaching career (Research, Society and Development, 2021)
Objective: To report the experience of academic monitoring as a collaborator in the development of teaching skills, from the perspective of the academic monitor. Method: This is a descriptive study, with a qualitative approach, an experience report type, based on the experiences of academic monitoring in the curricular component '' Human Histology '' taught at a Public University, located in Belém do Pará, addressed in the first semester in the undergraduate course in Nursing, during the years 2018 and 2019. Results: The experience as student-monitor favored the development of teaching skills such as teaching classes, use of active methodologies in the teaching-learning process; Communication; organization; understand about the responsibilities of the university professor; personal and professional planning; leadership; teamwork and, mainly, bonding and empathy with the monitor, making a professional critical and autonomous. Conclusion: Academic monitoring gives the student-monitor the opportunity to learn in addition to its curricular component, which requires constant updating and study by the student, for the sake of an effective performance, with the teacher, who supervises and guides in their functions, collaborating for the development of skills for a future higher teaching profession.